Potensi Perempuan Sentani, Papua: Sebuah Penelusuran Melalui Lantunan Lisan - Wigati Yektiningtyas Modouw (Balai Bahasa Provinsi Papua, 2019)
From ehabla, it is found that Sentani women are traditionally viewed as beautiful (penime/yoinine), kind hearted (ufoi/wafoi), cheerful (kui-kui/yale-yale), well-versed (afoi/faeufoi), gentle (nime), submissive (peu bam/yana bam), physically strong (ulae/walae), hard working (melifoi/mekaifoi), smart (itae/haba), and supportive to husbands. They are believed as kani (the earth) and play reproductive and productive roles through gardening, fishing and producing sago. Interestingly, the roles can be well and smartly managed.